Health Belief Model and Hypertension Prevention - Asep Sukohar; Suharmanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Hypertension is a cardiovascular disease that contributes to morbidity and mortality. Hypertension is the number one cause of death in the world every year. The prevalence of hypertension in the world in 2015 was 1.13 billion. The number of people with hypertension is increasing every year. By 2025 it is estimated that there will be 1.5 billion people affected by hypertension. Aim : This review summarizes the HBM used as an approach in the prevention of hypertension. Materials and Method : The article uses a questionnaire with a number of respondents between 18-403 with a total of 2,160. Results : Respondents are students, residents, nurses, police from Iran, London, USA, South Africa, and China. The HBM model is still relevant and feasible to be used in predicting hypertension prevention behavior. Conclusion : HBM is still relevant and feasible to use in predicting hypertension prevention behavior.